Metamorphosis in Red - Lang, Joanne; Lazure, Timothy (East Carolina University, 2019)
Folk and fairy tales have been told for centuries and they remain a mainstay in children's literature. When they were first written down, the tales included startling episodes of mistreatment of women, including sexual assault, oppression and violence. Though these stories have become sanitized over time, they still contain vestiges of the original written injustices. As a child, being read these narratives normalized this conduct and even as an adult, the stories continued to seem benign. Examining these tales more closely, especially the original versions, allows us to question the behaviors in the stories and related episodes in today's world. My thesis exhibition examines the well-known folk tale Little Red Riding Hood. Textiles, wall hangings, enameled wearable art, and a setting of handmade and found objects recreate emotions and themes from the tale. As they enter the installation, I ask the viewers to consider the challenges the girl protagonist faces through the various historical versions of the story. The exhibit culminates with my interpretation of the story's ending, a shift from the traditional views of Little Red Riding Hood.
Keywords: Grimm brothers; Textiles; Metal enameling; Fairy tales in art; Little Red Riding Hood (Tale)--Adaptations--Art; Feminism in art